UNOBSERVABLE EFFECTS AND SPEED OF ADJUSTMENT TO TARGET CAPITAL STRUCTURE - Matemilola, Bolaji Tunde; Noordin, Bany Ariffin Amin; Wan Ngah, Wan Azman Saini; Md Nassir, Annuar (International Journal of Business and Society, 2017)
The paper investigates whether unobservable firm-specific effects such as managerial ability is a major component of the target capital structure. We apply the system generalized method of moments that accounts for unobservable firm-specific effects. Our results reveal that unobservable firm-specific effects such as managerial ability are a major component that explains most of the cross-sectional variation in firms’ capital structure in Malaysia. Keywords: Capital Structure; Unobservable Effects; System GMM; Malaysia.